Fibrinogen is a ligand for the S. aureus MSCRAMM Bbp (Bone sialoprotein-binding protein). - FOSTER, TIMOTHY (My University, 2011)
MSCRAMMs (microbial surface components recognizing adhesive matrix molecules) are bacterial surface proteins mediating adherence of the microbes to components of the extracellular matrix of the host. On Staphylococci the MSCRAMMs often have multiple ligands. Consequently we hypothesized that the S. aureus MSCRAMM Bbp (bone sialoprotein-binding protein) might recognize host molecules other than the identified bone protein. A ligand screen revealed that Bbp binds human fibrinogen (Fg) but not Fg from other mammals. We have characterized the interaction between Bbp and Fg. The binding site of Bbp was mapped to residues 561-575 in the Fg A? chain using recombinant Fg chains and truncation mutants in Far Western blots and solid phase binding assays. Surface plasmon resonance was used to determine the affinity of Bbp for Fg. The interaction of Bbp with Fg peptides corresponding to the mapped residues was further characterized using isothermal titration calorimetry. In addition, Bbp expressed on the surface of bacteria mediated adherence to immobilized Fg A?. Also, Bbp interferes with thrombin-induced Fg coagulation. Together these data demonstrate that human Fg is a ligand for Bbp and that Bbp can manipulate the biology of the Fg ligand in the host.
PUBLISHED
Keywords: Immunology; Staphyllococcus aureus; Immunology, Inflammation & Infection